Minimally invasive crown lengthening with the bone reduction to minimize gingival recession - Neira N. Sakinah; Shafira Kurnia (Journal of Dentomaxillofacial Science, 2021)
ABSTRACTObjective: This case performs minimally invasive crown lengthening to minimize the incidence of gingival recession in the interdental area after the crown lengthening procedure. Methode: A patient has subgingival caries in teeth 12, 11, 22, and a lack of clinical crown length of tooth 22 for retention of the restoration. Clinical examination, radiographic photograph, and analysis of case models indicated the need for a crown lengthening procedure with a bone reduction to support the restoration. Crown lengthening was performed minimally invasive by maintaining the attachment of the papilla interdental of central incisors intact. The flap is only performed in areas that required bone reduction without breaking the attachment of the interdental gingiva. The bone reduction was performed using tungsten carbide bur. Results: One week after the crown lengthening showed fast healing and good repositioning of the gingival margins. After 3 months of crown lengthening showed no recession and no inflammation of the gingiva. Conclusion: This technique was effective to minimize gingival recession and increase the stability of the periodontal tissue after crown lengthening.